دراسات السلام: النشأة والتطور - بلهول، نسيم; فشار، عطاء الله أحمد (جامعة الجلفة, 2024)
سيتعرف المهتمين بمجال دراسات السلام من خلال هذه الدراسة على البحوث الخاصة بالسلام وأعمال أحد أشهر المساهمين وأكثرهم إنتاجا في هذا المجال، الأمر يتعلق ب "يوهان غالتونغ". الذي استعرض في الكثير من دراساته مسائل تتعلق بتطور دراسات السلام المعاصرة، ناهيك عن الأبحاث المتقدمة في مواضيع السلام والصراع، كما شملت أيضا إعادة تعريفه للعنف والسلام مع التوسع المستمر لنطاق دراسات السلام. نظرا للتطورات التي عرفتها مجالات البحث المشابهة لهذا النوع من الاهتمامات الأكاديمية، يمكن القول إن الإلتزام المعياري باللاعنف يعد سمة مميزة لدراسات السلام عن باقي المجالات المعرفية الاجتماعية منها. لتختتم الدراسة بعرض وجهتي نظر خاصة بدراسات السلام المعاصرة: أولاها، ترتبط بالمخاوف المتعلقة بعواقب اتساع نطاق دراسات السلام. أما الاتجاه الآخر، فيتعلق بقدرة هذا النوع من المجالات والاهتمامات العلمية على معالجة الأشكال المعاصرة للنزاعات المسلحة. Through this study, those interested in the field of peace studies will learn about peace research and the work of one of the most famous and prolific contributors to the field: Johan Galtung. In many of his studies, he reviewed issues related to the development of contemporary peace studies, not to mention advanced research on the topics of peace and conflict. It also included his redefinition of violence and peace with the continuous expansion of the scope of peace studies. Given the developments in research fields similar to this type of academic interest, it can be said that the normative commitment to nonviolence is a distinctive feature of peace studies from other social cognitive fields. The study concludes by presenting two points of view specific to contemporary peace studies: First, it is related to concerns regarding the consequences of the expansion of the scope of peace studies. The other trend relates to the ability of this type of scientific field and interest to address contemporary forms of armed conflict.
Keywords: ظاهرة العنف -- المنازعات المسلحة -- حقوق الإنسان -- السلام الدولي